Система Ga2Se3–In2Se3 - Олексеюк, И. Д.; Olekseyuk, I. D.; Иващенко, И. A.; Ivashchenko, I. A.; Гулай, Л. Д.; Gulay, L. D.; Данилюк, И. В.; Danulyk, I. V. (Волинський національний університет ім. Лесі Українки, 2010)
Методами рентгенофазового и дифференциально-термического анализов исследована квазибинарная система Ga2Se3–In2Se3. По результатам исследований и литературным данным по- строена её диаграмма состояния. Подтверждено существование фазы γ1, изоструктурной к γ-In2Se3 (пр. гр. Р61) и фазы γ2, которая кристаллизуется в той же пр. гр. Р61. The quasi-binary system Ga2Se3–In2Se3 was investigated by XRD and differential-thermal measurements. The diagram of phase equilibrium was constructed from the investigation results and literature data. The existence of γ1 phase, isostructural for γ-In2Se3 (sp. gr. Р61) and phase γ2, which crystallises in the same sp. gr. Р61 were confirmed.
The Specify of Interaction of Components in the Ga2Se3–In2Se3 System
Keywords: рентгенофазовий анализ; X-ray phase analysis; дифференциально-термический анализ; differential thermal analysis; система Ga2Se3–In2Se3; Ga2Se3–In2Se3 system